Current Assessment of the Effects of Environmental Chemicals on the Mammary Gland in Guideline Rodent Studies by the U.S. Environmental Protection Agency (U.S. EPA), Organisation for Economic Co-operation and Development (OECD), and National Toxicology Program (NTP) - Makris, Susan L. (National Institute of Environmental Health Sciences, 2010)
Background: Evaluation of the structural and/or functional integrity of the mammary gland (MG) across life stages is integral to the assessment of developmental, reproductive, and carcinogenic risk for environmental chemicals. Objectives: In this commentary I characterize MG assessment recommended in U.S. Environmental Protection Agency, Organisation for Economic Co-operation and Development, and National Toxicology Program guideline toxicology study protocols and identify any information gaps for the evaluation of MG development, structure, and function. Discussion: Several data gaps, issues, and challenges were identified. Current guidelines that include a lactation phase do not provide specific recommendations to record observations on maternal or offspring lactation or nursing behavior. In guideline studies, the assessment of MG toxicity often relies upon indirect, nonspecific, or surrogate end points, and information that could be useful in the interpretation of these data (e.g., mode of action or toxicokinetics) is often unavailable. Most guideline studies designed to assess general organ toxicity do not expose test animals during sensitive stages of MG development; histopathological evaluation of the developing MG is not routinely conducted; and evaluation of MG tissue for both sexes is inconsistently recommended. Conclusions: I propose the following general recommendations to enhance MG assessment in guideline toxicology studies: a) inclusion of more specific criteria for the evaluation of MG end points in guideline language, b) inclusion of histopathological evaluation of MG development (using whole-mount techniques) in existing or new guideline protocols that include offspring with perinatal and/or pubertal treatment, c) incorporation of perinatal exposures into rodent subchronic and carcinogenicity assays, and d) expansion of the histopathological evaluation of male MG tissue.